2021
DOI: 10.3389/fonc.2021.646217
|View full text |Cite
|
Sign up to set email alerts
|

LINC00470 Stimulates Methylation of PTEN to Facilitate the Progression of Endometrial Cancer by Recruiting DNMT3a Through MYC

Abstract: ObjectivesIncreasing researches emphasize the importance of long non-coding RNAs (lncRNAs) in the development of endometrial cancer (EC). There is wide recognition that LINC00470 is a critical participant in the tumorigenesis of cancers such as gastric cancer and glioblastoma, but its possible effects on EC progression remain to be explored.MethodsWe collected EC tissues and cells, where the expression of LINC00470 was determined, and followed by the Kaplan-Meier analysis of EC patient survival. We next examin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…[ 42 ] indicated that knockdown of LINC00470 expression inhibited cell proliferation and cell cycle progression, while overexpression of LINC00470 showed the opposite effects in hepatocellular carcinoma. In addition, LINC00470 promoted invasiveness, migration, and angiogenesis of endometrial cancer cells [ 43 ]. Knockdown of LINC00470 could significantly inhibit the melanoma cell proliferation and migration, and suppress the growth of tumor in vivo [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…[ 42 ] indicated that knockdown of LINC00470 expression inhibited cell proliferation and cell cycle progression, while overexpression of LINC00470 showed the opposite effects in hepatocellular carcinoma. In addition, LINC00470 promoted invasiveness, migration, and angiogenesis of endometrial cancer cells [ 43 ]. Knockdown of LINC00470 could significantly inhibit the melanoma cell proliferation and migration, and suppress the growth of tumor in vivo [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…We followed the specific steps as described in a previous publication [30]. Whole genomic DNA was extracted, and unmethylated cytosines in which were converted to uracil.…”
Section: Methylation-specific Pcr Detectionmentioning
confidence: 99%
“…For instance, LINC00470 facilitated phenotypes of gastric cancer cells via the promotion of PTEN mRNA degradation [28]. LINC00470 stimulated methylation of PTEN to facilitate the progression of endometrial cancer by recruiting DNMT3a via MYC [30]. LINC00470 directly interacted with FUS and repressed autophagy as an AKT activator to facilitate glioma cell phenotypes.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, regulating PTEN promotor methylation has been reported to play an important role in the progression of EC. The research of Yi et al, demonstrated that Linc00470 recruited DNMT3a through MYC to promote PTEN methylation and promote angiogenesis and metastasis of EC cells in vivo [ 112 ]. Chen et al, demonstrated that Piwil1 repressed PTEN expression through DNMT1-mediated PTEN hypermethylation in type I ECs [ 113 ].…”
Section: Tumor Suppressor Genesmentioning
confidence: 99%